Kajian pelan tempatan Kg. Padang Jawa : strategi dan cadangan - Norishak Ismail; Norliza Hashim; Wan Fakhruddin Ali; Zakaria Abdullah; Abd. Halim Abu; Azalai Ismail; Fudziah Abas; Hamiza Hamzah; Ismail Daud; Kalsom Yop Md. Kassim; Mahmud Alias; Mazyati Abd. Halim; et al. (Shah Alam : Institut Teknologi MARA, 1983)
PRZSL